2014
DOI: 10.1155/2014/764085
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Applications of Transition Metal Complexes of Benzothiazole Based Terpolymer: Synthesis, Characterization, and Effect on Bacterial and Fungal Strains

Abstract: Terpolymer of 2-amino-6-nitro-benzothiazole-ethylenediamine-formaldehyde (BEF) has been synthesized and characterized by elemental analysis and various spectral techniques like FTIR, UV-Visible, and 1H and 13C-NMR. The terpolymer metal complexes were prepared with Cu2+, Ni2+, and Zn2+ metal ions using BEF terpolymer as a ligand. The complexes have been characterized by elemental analysis and IR, UV-Visible, ESR, 1H-NMR, and 13C-NMR spectral studies. Gel permeation chromatography was used to determine the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Materials containing metal–polymer complexes possess intriguing mechanical and catalytic properties. Their potential applications include ion-conducting solid membranes used in batteries, semiconducting materials, pharmacological applications such as antibacterial and anti-inflammatory drugs, membranes for artificial organs, polymer catalysts, materials with tunable mechanical strength, and wastewater management . These materials contain metal atoms, which form reversible coordination bonds with polymer ligands ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Materials containing metal–polymer complexes possess intriguing mechanical and catalytic properties. Their potential applications include ion-conducting solid membranes used in batteries, semiconducting materials, pharmacological applications such as antibacterial and anti-inflammatory drugs, membranes for artificial organs, polymer catalysts, materials with tunable mechanical strength, and wastewater management . These materials contain metal atoms, which form reversible coordination bonds with polymer ligands ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared discs were dipped within a specified variation of free ligand, in addition to the complexes located within petri plates containing a nutrient medium sowed through every bacterial and fungal serum individually. Every plate was incubated for 24 and 48 h for the bacteria, as well as fungi, at 37 °C; furthermore, the zone of inhibition values were noted [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…P. Jana et al [28] reported that the peaks resonating at 3.2-2.4 ppm in the aminated carboxymethyl guar gum is due to protons of ethylenediamine. M. A. R. Ahamed reported that the signal obtained at 5.08 ppm in aminated polymer is assigned to -NH protons of ethylenediamine [31]. In the NMR spectra of niacin inulin complex prominent peaks arise from 9-7.5 ppm because of the protons at ortho, meta and para positions of the aromatic ring of niacin molecule.…”
Section: H-nmr Spectroscopymentioning
confidence: 99%